A Formalization of Minimalist Syntax. (18th January 2016) - Collins, Chris; Stabler, Edward
Abstract: The goal of this paper is to give a precise, formal account of certain fundamental notions in minimalist syntax. Particular attention is given to the comparison of token‐based (multidominance) and chain‐based perspectives on Merge. After considering a version of Transfer that violates the No‐Tampering Condition (NTC), we sketch an alternative, NTC‐compliant version.